Vulnerability - Liedo, Belén (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The notion of vulnerability is increasingly present in normative, legal and ethical documents of various kinds. The academic literature on the concept is recent and still in its consolidation stage. In general terms, a distinction can be made between two trends: the first, which reflects on «ontological vulnerability», shared by all human beings; and the second, on «social» or «situational vulnerability», generated in certain specific situations of injustice or oppression. This article presents a general approach to the use of the concept of vulnerability and the most prominent versions of the last decades. It also explores the relationship between vulnerability and three key ethical ideas: relational autonomy, responsibility and care. Emphasis is placed on the practical dimension of the discussion, related to the design of public policies and other tools for democratic governance.
Keywords: bioethics; care; public policies; relational autonomy; responsibility; vulnerability